Penerapan model project based learning (pjbl) untuk meningkatkan keaktifan belajar peserta didik pada pembelajaran IPA di kelas V sekolah dasar - Isti Nur Hidayah; Peduk Rintayati; Chumdari Chumdari (Didaktika Dwija Indria, 2023)
The aim of this classroom action research is to describe the application of the project based learning model and increase the active learning of students in class V at SDN Kalijoso. This research involved teachers and all fifth grade students at Kalijoso Elementary School, totaling 26 students. Interviews, documentation and observations were used to collect data. Source and technical triangulation is used to determine the validity of the data. Interactive data analysis as a data analysis method. The findings of this study show that the implementation of the project based learning model is carried out according to steps including (1) starting with basic questions, (2) making a product plan, (3) making a schedule, (4) monitoring, (5) testing product results, ( 6) evaluation of experience. The application of the Project Based Learning (PjBL) model can increase students' learning activeness through three cycles. The average pre-action learning activity was 31.95% then increased in the first cycle to 58% and increased in the second cycle to 76.27% and again increased in the third cycle to 88.45%.Kata kunci: project based learning, active learning, science learning, elementary school